Treatment of Large Osteochondral Lesions with Adjuvant Micronized Allogenic Cartilage Extracellular Matrix and Bone Marrow Aspirate Concentrate Reduces Rate of Postoperative Adjacent Cysts. Issue 4 (16th October 2019) - Drakos, Mark C.; Cabe, Taylor N.; Sofka, Carolyn; Kennedy, John; Deland, Jonathan
Category: Ankle, Arthroscopy, Sports Introduction/Purpose: Previous studies have established a correlation between the size of osteochondral lesions (OCLs) and the relative success of outcomes following surgical repair. Poorer results have been associated with traditional microfracture for lesions larger than 150 mm2. In these cases, osteochondral autograft transplantation (OAT) has shown to be a generally effective treatment despite associated disadvantages that include donor site morbidity, need to perform an osteotomy, and formation of postoperative adjacent cysts. The purpose of this study was to assess the effect of using a micronized allogenic cartilage extracellular matrix (ECM) mixed with bone marrow aspirate concentrate (BMAC) as an adjuvant therapy to augment and potentially improve the quality of repair achieved using OAT to treat larger lesions. Methods: Seventy cases (average age 38) treated by a fellowship-trained foot and ankle surgeon for an osteochondral lesion using OAT between December 2009 and June 2018 were identified. Retrospective chart review determined that 40 patients received adjuvant micronized ECM mixed with BMAC (average follow-up 25.6 months) while 30 had only BMAC injected into the joint or lesion (average follow-up 81.9 months). Preoperative lesion size, lesion location, and any concurrent injuries were also recorded. Foot and Ankle Outcome Scores (FAOS) were completed pre- and postoperatively through the prospective registry database at the authors' institution. Structural integrity of reparative cartilage was assessed on available postoperative MRIs using a modified magnetic resonance observation of cartilage repair tissue (MOCART) score. In addition, the presence of postoperative edema and adjacent cystic changes were recorded. Linear regression analysis was performed to analyze differences in MOCART scores, FAOS, postoperative rate of adjacent cysts, and postoperative rate of edema. Results: Twenty-four postoperative MRIs, average follow-up 14.04 (SD 9.52) months, were available for the ECM+BMAC adjuvant therapy group. Twenty-one MRIs, average follow-up 35.06 months (SD 28.41), were available for the non-adjuvant therapy group. 20.8% of the ECM+BMAC group exhibited signs of postoperative cysts compared to 60.9% of patients in the non- adjuvant therapy OAT group (p<0.01). Similarly, 66.7% of ECM+BMAC patients had edema postoperatively versus 90.5% of patients in the non-adjuvant therapy cohort (p = 0.05). MOCART scores were similar in each group: 68.33 (SD=15.99) in the OAT and ECM+BMAC group and 65.95 (SD=22.50) in the non-adjuvant therapy group. Finally, the post-operative FAOS Symptoms scores were significantly greater in patients receiving adjuvant therapy (p=0.03). Conclusion: Using micronized allogenic cartilage ECM mixed with BMAC to augment traditional OAT helps reduce the rate of postoperative adjacent cysts and edema. In addition, greater increases in patient reported functional outcome scores indicate this adjuvant therapy may help improve clinical outcomes. Application of this adjuvant therapy could be especially useful in allowing easier treatment of non-circular lesions of amorphous shapes. By improving integration of OAT into surrounding bone and reducing the rate of postoperative cysts, adjuvant therapy may improve long-term outcomes for large OCLs.